Global smoothness preservation and simultaneous approximation by multivariate discrete operators: Dedicated to Professor Gheorghe Coman on the occasion of his 80th anniversary - ANASTASSIOU, George A.; KESTER, Merve (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
In this article we study the multivariate generalized discrete singular operators defined on R N , N ≥ 1, regarding their simultaneus global smoothness preservation property with respect to Lp norm for 1 ≤ p ≤ ∞, by using higher order moduli of smoothness. Furthermore, we study their simultaneous approximation properties. Mathematics Subject Classification (2010): 26A15, 26D15, 41A17, 41A25, 41A28, 41A35, 41A80.